2020
DOI: 10.2147/rmhp.s233702
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluating Preferred and Perceived Leadership Styles of Nurse Managers Employed in Teaching Hospitals Affiliated to Yasuj University of Medical Sciences</p>

Abstract: Background and Objectives: Nurse Managers are required to apply leadership styles suited to the complicated and constantly changing healthcare system. This study aimed to compare the perceived and preferred perceptions of nursing personnel and managers toward leadership styles of nurse managers. Materials and Methods: This cross-sectional and analytical study was conducted on 341 subjects selected from nurse managers and staff employed in the teaching and treatment centers affiliated to YUMS, Yasuj, Iran. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…It was established in this present study that, nurse managers manifest their emotions by being aware of the structures of an organisation and knowing how to combine their leadership style with their emotions to attain organisational goals and manage subordinates indicated that, nursing leadership style influences leadership work effectiveness (29). Again evidence established that nurse managers who demonstrate democratic leadership styles are effective at remedying work pressure and challenges (30), thereby working to improve productivity (31) Hence a demonstration of manifestations of emotional intelligence in the working environment, as such findings agreed well. According to (32) the leadership styles of nurse managers help them to demonstrate professionalism in taking care of patients and improving situations and ensuring the well-being of patients.…”
Section: Discussionsupporting
confidence: 49%
“…It was established in this present study that, nurse managers manifest their emotions by being aware of the structures of an organisation and knowing how to combine their leadership style with their emotions to attain organisational goals and manage subordinates indicated that, nursing leadership style influences leadership work effectiveness (29). Again evidence established that nurse managers who demonstrate democratic leadership styles are effective at remedying work pressure and challenges (30), thereby working to improve productivity (31) Hence a demonstration of manifestations of emotional intelligence in the working environment, as such findings agreed well. According to (32) the leadership styles of nurse managers help them to demonstrate professionalism in taking care of patients and improving situations and ensuring the well-being of patients.…”
Section: Discussionsupporting
confidence: 49%